Consumer Purchasing Decisions of Teh Pucuk Harum : Product Quality, Advertising and Brand Image - Surya Bintarti; Suwandy Suwandy (STIE Binaniaga, 2021)
Teh Harum Pucuk drink is one of the ready-to-drink tea drinks that are packed with great experience from previous years, so that they can compete with other packaged ready-to-drink tea drinks. Fans of ready-to-drink tea packages come from various circles, including students, workers, the general public, and college students. This review plans to examine the impact of the quality of goods, publications and brands in general on the Purchasing Decision of fragrant shoots tea products. The testing technique used is non-likelihood inspecting, specifically the purposive testing strategy. The examples in this review are 75 individuals, especially individuals who have purchased ready-to-drink tea drinks that are bundled with the brand of Teh Pucuk Wangi and information is collected by distributing Google from polls, the information collected is tested for validity with legitimacy and steadfast quality tests, information investigation procedures using the PLS program. The results of a helpless exploration show that the quality of goods and publicity factors in ready-to-drink foods bundled with teh pucuk wangi has a positive effect on purchasing choices, and brand image has a negative effect on purchasing choices of pucuk harum.